PERSEPSI SISWA TERHADAP KEGIATAN MANJEMEN KELAS OLEH GURU DI SMK PLUS BINA NUSANTARA MANDIRI KOTA PARIAMAN - SUCI DARMAYANTI (Universitas Negeri Padang, 2016)
The goal of the research were to get information about classroom management activities by teachers. The type of research is descriptive research. The population was all of the students in the class XI and XII SMK PLUS Bina Nusantara Mandiri Pariaman as much 100 people and the sample was 80 people. Sampling technique using krejcie table. The instrument of the research was a questionnaire likert scale models that have been tested for validity and reliability. The result of this research is classroom management activities by teachers in the SMK PLUS Bina Nusantara Mandiri pariaman stay in pretty good.